2018
DOI: 10.5056/jnm18040
|View full text |Cite
|
Sign up to set email alerts
|

Role of High-affinity Choline Transporter 1 in Colonic Hypermotility in a Rat Model of Irritable Bowel Syndrome

Abstract: Background/AimsIrritable bowel syndrome (IBS) is a common disease characterized by intestinal dysmotility, the mechanism of which remains elusive. We aim to determine whether the high-affinity choline transporter 1 (CHT1), a determinant of cholinergic signaling capacity, modulates intestinal motility associated with stress-induced IBS.MethodsA rat IBS model was established using chronic water avoidance stress (WAS). Colonic pathological alterations were evaluated histologically and intestinal motility was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…7 Until now there are no data on how central CRF signaling interacts with peripheral CRF. However, there is evidence that peripheral CRF acts on myenteric neurons that determine the activity of gastric and colonic functions during stress, [29][30][31] and further studies are needed to elucidate these issues. Gastric motility consists of 2 motor patterns: postprandial contractions and interdigestive contractions.…”
Section: Discussionmentioning
confidence: 99%
“…7 Until now there are no data on how central CRF signaling interacts with peripheral CRF. However, there is evidence that peripheral CRF acts on myenteric neurons that determine the activity of gastric and colonic functions during stress, [29][30][31] and further studies are needed to elucidate these issues. Gastric motility consists of 2 motor patterns: postprandial contractions and interdigestive contractions.…”
Section: Discussionmentioning
confidence: 99%
“…Mediators of colonic mucosa in IBS patients have been demonstrated to activate ACh release from myenteric neurons via mast cells independently of the bowel habit [ 147 ]. Hyperalgesia and visceral hypersensitivity have been associated with increased expression of high-affinity choline transporter (HAChT) [ 148 ]. This augmentation can result in an increase in ACh levels, which has an antinociceptive role [ 149 ].…”
Section: Acetylcholinementioning
confidence: 99%
“…This is consistent with the observation of deformed sloppy stool excreted by the IBS rats. The data indicated that the modelling of IBS-D was established successfully [32]. After treatments with either HPM or PBT, the animals showed significant decreased BSF scale scores ( p < 0.05) and FWC ( p < 0.05) with a firmer stool form as compared to the IBS group.…”
Section: Resultsmentioning
confidence: 99%